Tools and tactics to define specificity of metabolic chemical reporters - Mukherjee, Mana Mohan; Bond, Michelle R.; Abramowitz, Lara K.; Biesbrock, Devin; Woodroofe, Carolyn C.; Kim, Eun Ju; Swenson, Rolf E.; Hanover, John A. (Frontiers in Molecular Biosciences, 2023)
Metabolic chemical reporters (MCRs) provide easily accessible means to study glycans in their native environments. However, because monosaccharide precursors are shared by many glycosylation pathways, selective incorporation has been difficult to attain. Here, a strategy for defining the selectivity and enzymatic incorporation of an MCR is presented. Performing belimination to interrogate O-linked sugars, as well as using commercially available glycosidases and glycosyltransferase inhibitors, we probed the specificity of widely used azide (Ac4GalNAz) and alkyne (Ac4GalNAlk and Ac4GlcNAlk) sugar derivatives. Following the outlined strategy, we provide a semiquantitative assessment of the specific and nonspecific incorporation of this bioorthogonal sugar (Ac4GalNAz) into numerous N-and O-linked glycosylation pathways. This approach should be generally applicable to other MCRs to define the extent of incorporation into the various glycan species.